Bird Community Structure (Avifauna) in The Coastal Forest Area of Baluran National Park - Siska Ayu Wulandari; Agus Santoso (Journal of Biological Science and Education, 2020)
Baluran National Park is a Natural Resources Conservation area. Avifauna is a perfect indicator to determine environmental health and the value of biodiversity as a whole. This study aimed to assess the diversity of avifauna species and their abundance in Baluran National Park. This research using a combination line transect and point count method. The results showed that Baluran National Park has high species diversity. Species found during the study were 36 of 24 families. As many as 11% (4 species) of birds are in a large category, 39% (14 species) in a general category, 19% (7 species) in a frequent category, 6% (2 species) in an uncommon category and 25% (9 species) in a rare category. Based on the research results, it can be concluded that there are various kinds of avifauna in Baluran National Park.Keywords: Avifauna, Baluran National Park, Diversity, Line Transect, Point Count.